Social Bond Emerges as Primary Factor in Logistics Customer Loyalty: Social Bond Menjadi Penentu Loyalitas Pelanggan di Industri Logistik - Lailatul Ikhsanti; Jojok Dwiridotjahjono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The logistics industry operates in a highly competitive environment, where maintaining customer loyalty is essential for sustainable growth. Specific Background: In Indonesia, particularly Batam, logistics companies face challenges in retaining clients amid increasing service alternatives. Knowledge Gap: While prior research has addressed customer loyalty in various service sectors, limited studies have examined the combined role of social, structural, and financial bonds in shaping loyalty within logistics services. Aims: This study investigates the influence of social bond, structural bond, and financial bond on customer loyalty at PT Threelog Kencana Mandiri. Results: Using a quantitative causal design with 56 respondents and analyzing data through PLS-SEM, findings reveal that all three variables positively and significantly affect customer loyalty, with social bond being the most dominant factor. Collectively, the three bonds explain 77% of the variation in customer loyalty, indicating a strong category. Novelty: The study highlights that beyond financial incentives, loyalty in logistics is largely driven by relational and systemic bonds. Implications: These results suggest that logistics firms should strengthen social interactions and service structures alongside financial offerings to build sustainable customer loyalty. Highlights: Social bond is the strongest driver of loyalty. Structural and financial bonds also significantly influence customers. Combined, the three factors explain 77% of loyalty variation. Keywords: Customer Loyalty, Social Bond, Structural Bond, Financial Bond, Logistics Industry